Morality in research: Views on the questionnaire for examining Moral, Legal and Religious aspects of research projects - SM Seyed Fatemi (JRI, 2002)
The questionnaire of morality in biotechnological research that has been drafted by this writer includes four sections dealing with various aspects of a research in this field. The first section contains general questions such as the aim and the anticipated achievement(s) of the research. The second section includes question concerning the subject. Regarding the human being as the subject of research the questionnaire is mainly concerned with such issues as informed consent, confidentiality, health and the safety of the subject. The third section is dealing with the issues of the safety and the health of researchers(s) themselves. Finally the forth section is concentrating on such questions as environmental concerns and the like. I have offered in this Article some explanations about moral principles underling the questionnaire.
Keywords: Questionnaire, Morality, Bioethics, Research